2013
DOI: 10.1088/0004-637x/770/1/3
|View full text |Cite
|
Sign up to set email alerts
|

Um 625 Revisited: Multiwavelength Study of a Seyfert 1 Galaxy With a Low-Mass Black Hole

Abstract: UM 625, previously identified as a narrow-line active galactic nucleus (AGN), actually exhibits broad Hα and Hβ lines whose width and luminosity indicate a low black hole (BH) mass of 1.6 × 10 6 M . We present a detailed multiwavelength study of the nuclear and host galaxy properties of UM 625. Analysis of Chandra and XMM-Newton observations suggests that this system contains a heavily absorbed and intrinsically X-ray weak (α ox = −1.72) nucleus. Although not strong enough to qualify as radio loud, UM 625 does… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 108 publications
1
15
0
Order By: Relevance
“…The right bottom subplot shows the z = 2, 5 and 7 Magorrian relations of the Tiamat result with thick lines compared with the z ∼ 0.6 Tiamat-125-HR Magorrian relation. Observations from the local Universe are indicated with different symbols (Thornton et al 2008;Jiang et al 2011;Mathur et al 2012;Jiang et al 2013;Reines et al 2013;Scott et al 2013;Busch et al 2014;Sanghvi et al 2014;Yuan et al 2014). We see that the model predicts a similar Magorrian relation at z ∼ 0.6 compared to the local observations and we find an increasing normalization towards lower redshifts in the mass range of 10 10 M < M * < 10 12 M .…”
Section: Black Hole Propertiessupporting
confidence: 51%
“…The right bottom subplot shows the z = 2, 5 and 7 Magorrian relations of the Tiamat result with thick lines compared with the z ∼ 0.6 Tiamat-125-HR Magorrian relation. Observations from the local Universe are indicated with different symbols (Thornton et al 2008;Jiang et al 2011;Mathur et al 2012;Jiang et al 2013;Reines et al 2013;Scott et al 2013;Busch et al 2014;Sanghvi et al 2014;Yuan et al 2014). We see that the model predicts a similar Magorrian relation at z ∼ 0.6 compared to the local observations and we find an increasing normalization towards lower redshifts in the mass range of 10 10 M < M * < 10 12 M .…”
Section: Black Hole Propertiessupporting
confidence: 51%
“…In Figure 1, we highlight three famous Seyfert 1 galaxies, NGC 4395, POX 52, and UM 625, to show where they fall on the diagram (yellow circles). As discussed above, NGC 4395 has the only dynamical mass measurement of a CMBH in a dwarf galaxy (den Brok et al 2015), POX 52 has a robust CMBH mass estimate (Barth et al 2004) and UM 625 is a Seyfert 1 galaxy hosting a low-mass CMBH (Jiang et al 2013). It should be noted that UM 625 was added manually, and is not part of our sample as it is neither a dwarf nor nearby, though its low-mass CMBH still makes it an object of interest.…”
Section: Existing Cataloguesmentioning
confidence: 99%
“…A few recent papers (e.g. Jiang et al 2011a;Jiang et al 2013;Mathur et al 2012;Reines et al 2013) have, however, shown that there is an offset at the low mass end of the M bh -M sph diagram, such that the black hole mass is lower than predicted by the near-linear M bh -M sph relation established using galaxies having predominantly higher mass black holes. These offset galaxies have been labelled by some to contain pseudobulges -spheroidal components thought to be produced by the secular evolution of a disk and associated with bars (Bardeen 1975;Hohl 1975;Hohl & Zang 1979;Combes & Sanders 1981;Kormendy 1982Kormendy , 1993Kormendy & Kennicutt 2004).…”
mentioning
confidence: 98%